2013
DOI: 10.1097/01.id.0000434274.22605.b6
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Survival Rate Outcomes of Innovative Dental Implants

Abstract: The new implant design showed good results for 1 year of follow-up, comparable with the literature, and could be a good choice for every implant-based procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Ten studies 23,25,27,37,41,42,47,51,66,76 j o u r n a l o f d e n t i s t r y x x x ( 2 0 1 4 ) x x x -x x x reported the presence of diabetic patients. Nine studies 7,8,25,28,30,36,51,57,72 reported the inclusion of periodontally compromised patients in their studies. Periodontitis was an inclusion criterion for all patients in three studies.…”
Section: Description Of the Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…Ten studies 23,25,27,37,41,42,47,51,66,76 j o u r n a l o f d e n t i s t r y x x x ( 2 0 1 4 ) x x x -x x x reported the presence of diabetic patients. Nine studies 7,8,25,28,30,36,51,57,72 reported the inclusion of periodontally compromised patients in their studies. Periodontitis was an inclusion criterion for all patients in three studies.…”
Section: Description Of the Studiesmentioning
confidence: 98%
“…All implants were immediately loaded in thirty-one studies. 3,8,9,14,19,20,22,24,27,29,31,32,34,[37][38][39]46,47,49,52,53,55,56,59,61,62,65,66,69,71,75 In seventeen studies 5,16,17,21,23,25,30,33,35,36,40,50,57,60,68,72,77 the implants were immediately or delayed loaded, and three studies 48,70,76 did not provide information about the healing/loading time. In one study …”
Section: Description Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations